1998
DOI: 10.1037/0278-7393.24.4.862
|View full text |Cite
|
Sign up to set email alerts
|

Initial phoneme versus whole-word criterion to initiate pronunciation: Evidence based on response latency and initial phoneme duration.

Abstract: Undergraduates participated in 4 speeded naming experiments investigating 2 criteria to initiate articulation-initial phoneme (IP) or whole word (WW). These criteria make different response latency and IP duration predictions for words with regular versus irregular vowel pronunciations (e.g., "pump" vs. "pint"). The IP criterion predicts no latency differences but longer IP durations for irregulars, whereas the WW criterion predicts no IP duration differences but longer latencies for irregulars. The latencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(168 citation statements)
references
References 51 publications
8
158
0
Order By: Relevance
“…6. There is emerging evidence that subjects can initiate their articulation prior to computing the entire pronunciation of a word (Kawamoto, Kello, Jones, & Bame, 1998). Note, however, that the most difficult aspect of mapping orthography to phonology in English relates to inconsistency in vowel pronunciations, and the fixation measure used in the current simulation is sufficiently sensitive to reflect this property.…”
Section: Discussionmentioning
confidence: 98%
“…6. There is emerging evidence that subjects can initiate their articulation prior to computing the entire pronunciation of a word (Kawamoto, Kello, Jones, & Bame, 1998). Note, however, that the most difficult aspect of mapping orthography to phonology in English relates to inconsistency in vowel pronunciations, and the fixation measure used in the current simulation is sufficiently sensitive to reflect this property.…”
Section: Discussionmentioning
confidence: 98%
“…In line with cascaded flow of information, studies of spontaneous speech corpora have found frequency effects on articulation durations (Gahl, 2008;Pluymaekers, Ernestus, & Baayen, 2006). In single word production, a longer duration of the initial phoneme has been reported for words entailing irregular vowel pronunciation, compared to words with a regular vowel pronunciation (Kawamoto, Kello, Jones, & Bame, 1998). Also, lexical frequency seems to affect initial phoneme durations, but not rhyme durations (Kawamoto, Kello, Higareda, & Vu, 1999; see also Mousikou & Rastle, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…in the first keystrokes. Indeed, this prediction has been already considered in typing (Damian & Freeman, 2008), and more thoroughly discussed and examined in spoken production (e.g., Kawamoto et al, 1998;. As suggested by an anonymous reviewer, we performed additional analyses in which we separately considered the average interkeystroke intervals corresponding to the first and the second half of each response.…”
Section: For Both Rts and Mean Ikis We Performed Analyses Using Residmentioning
confidence: 99%
“…Unfortunately, it was not possible to control for factors such as articulatory difficulty (e.g., initial phoneme) and voice-key sensitivity (e.g., factors causing the voice-key to trigger). These factors are known to potentially affect naming latencies (e.g., Kawamoto, Kello, Jones, & Bame, 1998;Kessler, Treiman, & Mullennix, 2002;Pechmann, Reetz, & Zerbst, 1989;Rastle & Davies, 2002). Therefore, we carried out an additional experiment including a delayed naming task to control for potential differences of these two factors.…”
Section: Discussionmentioning
confidence: 99%